2022
DOI: 10.1002/ejp.2013
|View full text |Cite
|
Sign up to set email alerts
|

Severe low back or lower limb pain is associated with recurrent falls among older Australians

Abstract: Background: Few studies have explored the impact of low back or lower limb pain severity on recurrent (≥2) falls in older adults. Objectives: Investigate the association between the severity of low back or lower limb pain, and ≥2 falls or falls-related injuries. Methods: Community-dwelling Australian males and females in the ASPREE Longitudinal Study of Older Persons (ALSOP), aged ≥70 years. Self-reported, cross-sectional questionnaire data regarding number of falls and falls-related injuries in the last 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…A high hazard ratio was also observed between moderate-to-severe chronic pain and fall-related injuries with chronic pain. Recent studies examining the association between pain and falls have found that severe low back or lower limb pain is associated with fall-related injuries in women [43], a nding supported by the present study. Although the underlying mechanisms of the association between chronic pain severity and fall-related injuries are unknown due to the paucity of studies, the results of this study indicate that reducing chronic pain severity is important in preventing fall-related injuries.…”
Section: Discussionsupporting
confidence: 89%
“…A high hazard ratio was also observed between moderate-to-severe chronic pain and fall-related injuries with chronic pain. Recent studies examining the association between pain and falls have found that severe low back or lower limb pain is associated with fall-related injuries in women [43], a nding supported by the present study. Although the underlying mechanisms of the association between chronic pain severity and fall-related injuries are unknown due to the paucity of studies, the results of this study indicate that reducing chronic pain severity is important in preventing fall-related injuries.…”
Section: Discussionsupporting
confidence: 89%
“… 11 Similarly, older men and women reporting severe lower-limb pain on most days were 100% and 40% more likely to report recurrent falls in the past year, respectively, as compared with peers with mild pain; older men and women reporting severe LBP on most days, were 70% and 50% more likely to report recurrent falls, respectively. 40 …”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have examined chronic pain and multisite pain as a risk for falls in older adults living in the community. 5,[9][10][11]13,14 A recent study on community-dwelling older adults aged ≥70 years found that lower back or lower limb pain was associated with an increased risk of frequent falls and fall-related injuries. 14 The context of related injuries involves not only the site of pain in the body but also the severity of pain.…”
Section: Introductionmentioning
confidence: 99%
“…5,[9][10][11]13,14 A recent study on community-dwelling older adults aged ≥70 years found that lower back or lower limb pain was associated with an increased risk of frequent falls and fall-related injuries. 14 The context of related injuries involves not only the site of pain in the body but also the severity of pain. A population-based cohort study examined the relationship between severity of chronic pain and risk for injurious falls in older adults aged ≥70 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation